Об оптимизации прямых методов решения интегральных уравнений Фредгольма II-рода с ядрами бесконечной гладкости - Урумбаев, А.Н. (Український математичний журнал, 1993)
We give a direct method, optimal in Lof solving the Fredholm integral equation of the second kind with operators acting in the space of functions harmonic on a disk or in the space of function analytically extendable onto an infinite strip. For this method, an exact order of the error is obtained.